2015
DOI: 10.1007/s10750-015-2465-0
|View full text |Cite
|
Sign up to set email alerts
|

Habitat complexity and food item size modify the foraging behaviour of a freshwater fish

Abstract: 26The functional response describes the relationship between feeding rate and prey density, and 27 is important ecologically as it describes how the foraging behaviour of an animal changes in 28 response to food availability. The effects of habitat complexity and food item size was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 67 publications
0
12
0
1
Order By: Relevance
“…Species-specific foraging may be on account of the flexible choice of the predator (Chick and McIvor 1997;Valinoti et al 2011;Lyons et al 2016) and prey (Gotceitas and Colgan 1989;Ostrand et al 2004;DeBoom and Wahl 2013) in different refuge habitats. To gain maximal net energy in variable habitats, predators might alter their hunting modes with the changes in choice and distribution of prey, regardless of its predation type (Savino and Stein 1989a;Scharf et al 2006;Murray et al 2016). For example, in a low complexity habitat, lined seahorse, fish assemblages in the Novigrad Sea, and larvae of the diving water beetle (Dytiscus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Species-specific foraging may be on account of the flexible choice of the predator (Chick and McIvor 1997;Valinoti et al 2011;Lyons et al 2016) and prey (Gotceitas and Colgan 1989;Ostrand et al 2004;DeBoom and Wahl 2013) in different refuge habitats. To gain maximal net energy in variable habitats, predators might alter their hunting modes with the changes in choice and distribution of prey, regardless of its predation type (Savino and Stein 1989a;Scharf et al 2006;Murray et al 2016). For example, in a low complexity habitat, lined seahorse, fish assemblages in the Novigrad Sea, and larvae of the diving water beetle (Dytiscus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed that free-floating macrophytes covered much of the water surface during summer, whereas the middle and bottom layers of the water column were essentially devoid of aquatic macrophytes. Habitats that are relatively simple in structure not only intensify competitive interactions between rotifer communities [48], but also favor the foraging activities of potential predators such as fish [49]. Both of these factors contribute to decreases in rotifer density.…”
Section: Seasonality Of Microhabitat Structures That Support Rotifer mentioning
confidence: 99%
“…Na literatura que reporta experimentos ecológicos, a espécie utilizada como presa geralmente é aclimatada nas condições experimentais por períodos que variam de 8 a 72 h (e.g., FIGUEIREDO et al, 2015), enquanto peixes predadores são aclimatados por pelo menos 14 dias (e.g. MURRAY et al, 2016 SILVA, 2014).…”
Section: Alguns Pontos Essenciais De Um Experimento Manipulativounclassified